Osteogenic Melanoma With Desmin Expression. (July 2017) - Trevisan, Flávia; Tregnago, Aline C.; Lopes Pinto, Clóvis A.; Urvanegia, Ana C. M.; Morbeck, Diogo L.; Bertolli, Eduardo; Riva Neto, Floriano R.; Duprat Neto, João P.; de Macedo, Mariana P.
Abstract : Background: Osteogenic differentiation is rarely seen in melanomas, when it occurs it is mainly in acral lesions. Methods: We report a case of an osteogenic melanoma in a 49-year-old woman who presented with a pigmented lesion in the subungueal region of her left hallux. The lesion was ulcerated and infiltrated until the deep dermis without bone involvement. Results: The tumor was composed of pleomorphic atypical epithelioid and fusiform cells disposed in nests or cords, with vesicular nuclei and prominent central nucleoli. Focal lentiginous proliferation of large atypical melanocytes was present along the dermoepidermal junction. Areas of osteoid matrix focally mineralized were disposed in trabeculae, and there were islands of neoplastic cells. Immunohistochemistry revealed strong expression of S-100 protein and, unexpectedly, of desmin. Focal expression of Melan-A, microphthalmia transcription factor, and HMB-45 is also revealed. Mutations in BRAF and NRAS genes were not present. The patient was submitted to an amputation of the left hallux with negative sentinel lymph node. Conclusion: The importance of recognizing osteogenic melanoma is based on difficulties for histologic recognition and its differentials diagnosis.